PENGEMBANGAN MODEL PENILAIAN KINERJA PEGAWAI - Awang Anwaruddin1 (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2006)
In this globalization era, where strategic change and technology development happen so fluctuated and unpredictable, the management of civil servants needs such a specific and accommodative strategic. Through Law Number 43 Year 1999 on the Personnel Policy, the heads of institutions in the central and local government has got an access to manage the civil servants professionally, including the evaluation of their performance. It is declared in the law that the performance evaluatuon for civil servants should be effectively, accurately, flexibly and implemented. However, the on-going evaluation method does not fully accomodate the rules, especially in adapting the progress of the professionalism era. Besides, the method is often implemented ineffectively by the rating officials. This article attempts at discussing such malpractices and biases in the process of performance evaluation for the civil service. By the end of the article, a chapter on the future-oriented evaluation is presented as the alternative instrument to the performance evaluation method, esecially when an employee is focused on a future performance or position in his institution.